Journal of medieval military history. - France, John; DeVries, Kelly, 1956-; Rogers, Clifford J. (The Boydell Press, 2020)
"The Journal of Medieval Military History continues to consolidate its now assured position as the leading academic vehicle for scholarly publication in the field of medieval warfare." Medieval Warfare.